An Effective Biclique Enumeration Algorithm Using Divide and Conquer - T. Nithya, E. Ramaraj, V. Sameswari (International Journal of Advanced Science and Technology, 2020)
Recently, web mining plays an important role in mining the exact data from the larger web. The existing algorithms afford lot of problems at some point of the execution of the method takes a lot of time to process the data with lesser speed. To overcome the disadvantages, the research work proposes a new technique named as Effective Biclique Enumeration Algorithm with the help of the Divide and Conquer method (EBEA-DAC). The proposed method produces a higher speed process and delivery of the data with minimal time as well as without an overloading issue; it produces more accurate data than the existing Biclique Enumeration Algorithm. The method is is compared with significant parameters of existing and proposed approaches such as True Positive Rate, False Positive Rate, Precision, F-Measure, Receiver Operating Characteristics Area, Matthews Correlation Coefficient and Recall.